PENGARUH BRAND IMAGE, HARGA, KUALITAS PRODUK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA XIAOMI SMARTPHONE (STUDY PADA KONSUMEN XIAOMI, METEOR CELL KOTA MALANG) - Muhammad Waliyul Ilmi; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to determine and analyze the effect of brand image, price, product quality, and WOM both simultaneously and partially on the decision to buy a Xiaomi mobile phone in Meteor Cell Malang. The population in this study is the number of consumers in April, which is 1,700 which shows the average number of buyers each month. While the number of samples taken was 73 respondents.The results of simultaneous analysis shows that the influence of brand image variables, prices, product quality and WOM has a significant influence on the purchase decision of Xiaomi mobile phones. While partially brand image, price, product quality and word of mouth have a significant effect on purchasing decisions for xiaomi cellphones. Keywords: Brand Image, Price, Product Quality, WOM, Purchasing Decisions